MEASURING THE IMPACT OF EIT-4-BPSD ON QUALITY OF LIFE AMONG RESIDENTS: RECOMMENDED APPROACH. (11th November 2018) - Van Haitsma, K; Resnick, B; Galik, E; Kolanowski, A; Boltz, M; Behrens, L
Abstract: Challenges to measuring quality of life of residents' with dementia include their ability to provide subjective input, evaluators' knowledge of what is relevant, and potential biases when proxy reporting is done. The Quality of Life in Late-Stage Dementia (QUALID) was developed specifically for individuals with late-stage dementia. We tested the psychometric properties of QUALID using a Rasch measurement model with 137 nursing home residents from 14 nursing homes. There was evidence of internal consistency with a Cronbach alpha of .89 and all items but one fit the model. There was a significant relationship between quality of life and depressive symptoms (r=.71, p=.001), pain (r=.26, p=.01), function (r=-.19, p=.03), and agitation (r=.56, p=.001). The categories were appropriately used. Item mapping suggested a need for easier items to differentiate those low in quality of life. The findings provided support for use of the QUALID with nursing home residents with dementia.